Nadciśnienie tętnicze – istotny problem chorych z cukrzycą - Głuszek, Jerzy; Kosicka, Teresa (Przewodnik Lekarza/Guide for GPs, 2006)
The incidence of hypertension in diabetes is 2-3 frequently than in whole human population. It is often connected with diabetic nephropathy, which is leading to end-stage renal disease, so antihypertensive treatment should be individually adapted to particular indications. The patients should be train to non pharmacological treatment especially dietetic. The presented paper reviews different, often controversial diets. The most important goal in the therapy is lower blood pressure, but the choice of the drug is insignificant matter. According to great clinical trials in hypertension management can be use all groups of drugs to lower blood pressure. In large prospective randomized studies in diabetes has been shown that either angiotensin converting enzyme inhibitors or angiotensin II antagonist are the best drugs, which delay the onset of micro- and macroalbuminuria and prevent end-stage renal disease.